Evolutional conservation of molecular structure and antiviral function of a type I interferon, IFN-kappa, in poultry. (December 2018) - Gao, Mingchun; Guo, Yongli; Du, Jiwen; Song, Zhifeng; Luo, Xiuxin; Wang, Junwei; Han, Wenyu
Abstract: IFN-kappa (IFN-κ) is a type I IFN expressed by keratinocytes, monocytes and dendritic cells with important roles during the innate immune response period. This research was conducted to elaborate the evolution and characteristics of IFN-κ in poultry. Chicken IFN-κ is located on the sex-determining Z chromosome, which is greatly different from mammals. Poultry IFN-κ cluster together in a species-specific manner through positive selection pressure and share only 19–33% homology with mammalian IFN-κ and poultry other type I IFN. Both chicken and duck IFN-κ was constitutively expressed in spleen, skin, lung, and peripheral blood mononuclear cells (PBMC), as well as being significantly induced after treatment with virus in PBMC. Biologically, poultry IFN-κ has antiviral activity against VSV in chicken embryonic fibroblasts and duck embryonic fibroblasts (CEF and DEF) cells, and induces the expression of IFN stimulated genes (ISGs). After treatment with JAK1 inhibitor, the ISGs expression can be down-regulated. Overall, our research on poultry IFN-κ not only enriches the knowledge about IFN-κ but also facilitates further research on the role of type I IFNs in antiviral defense responses in poultry. Highlights: Poultry IFN-κ type I interferon locus was constructed and analyzed. Poultry IFN-κ gets through positive selection pressure. Poultry IFN-κ was highly transcribed in spleen, skin, lung, and peripheral blood mononuclear cells. Poultry IFN-κ has antiviral activity against VSV on CEF and DEF cells. Poultry IFN-κ can exerted antiviral activity through JAK-STAT pathway.